2006
DOI: 10.1097/01.all.0000244799.33734.d4
|View full text |Cite
|
Sign up to set email alerts
|

Ocular cicatricial pemphigoid

Abstract: OCP remains a difficult disease to manage well and the progress being made in understanding disease mechanisms is whence true disease-modifying, safe therapy is likely to emerge in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The destruction of Vogt Palisades and limbal stem cells deficiency could be similarly found in other chronic inflammation on ocular surface such as Stevens-Johnson syndrome and cicatricial ocular pemphigoid. 19,20 However, the relationship between the duration and severity of VKC and the degree of Vogt Palisades destruction requires further investigation with a large number of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The destruction of Vogt Palisades and limbal stem cells deficiency could be similarly found in other chronic inflammation on ocular surface such as Stevens-Johnson syndrome and cicatricial ocular pemphigoid. 19,20 However, the relationship between the duration and severity of VKC and the degree of Vogt Palisades destruction requires further investigation with a large number of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A typical positive result will reveal in the epithelial basement membrane a linear deposition of different immunoglobulins (IgG, IgA, IgM) and complement 3 proteins. Still, 20-40% of patients have a negative biopsy result that does not rule out the diagnosis ( 14 , 15 ). Radioimmunoassay and immunoblot techniques can identify the circulating autoantibodies in active disease while classic indirect immunofluorescence is not helpful.…”
Section: Diagnosis and Classificationmentioning
confidence: 99%
“…There have been some reported cases of CP triggered by human immunodeficiency virus, diphtheria vaccination, and some medications such as methyldopa, clonidine, and D-penicillamine [110,111]. In addition, other autoimmune diseases may occur more frequently in patients with CP [112]. Moreover, some bullous diseases may indicate the presence of an underlying malignancy.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…These patients are clinically indistinguishable from other autoimmune bullous diseases. Specialized immunopathologic studies and/or IEM may be required for diagnosis [112,125]. It also has been reported that ocular CP developed after Steven Johnson syndrome and Lyell syndrome in some cases.…”
Section: Differential Diagnosismentioning
confidence: 99%